Investigating the Relationship between Leadership Styles and Positive Organizational Behavior and Stress of COVID 19 - Mehri Zadeh Hosseini; Zohreh Karimiankakolaki (Journal of Social Behavior and Community Health)
Background: Leadership style is a specific behavioral pattern that is constantly manifested during organizational work and others recognize that person. This study investigated the relationship between leadership styles and positive organizational behavior and stress of COVID-19 in the staff of Shahrekord Health Centers in 2021. Methods: This research was an applied descriptive correlational study. The sample included 148 people from the staff of Shahrekord health centers in 2021. The participants were selected randomly. The tools used in this research were three questionnaires: Likert leadership style questionnaire, Lutans positive attitude organizational behavior questionnaire, and COVID-19 stress questionnaire. Data were analyzed with SPSS20 using descriptive statistics and Pearson correlation test. Results: According to the results, the majority of participants were in the age range of 30 to 35 years, the mean score of leadership style was 86.75 that was high. The mean score of positive organizational behavior was 79.23 that was high, and the mean score of stress of COVID19 was 7.23 that was low. The mean score of leadership style in all cases was positively and significantly correlated with the score of positive organizational behavior (r=0.322, P<0.001) and inversely correlated with the score of stress of COVID-19 (r=-0.314, P<0.001).  Also, the mean score of positive organizational behavior was inversely correlated to the score of stress of COVID19 (r=-0.374, P<0.001). Conclusion: Positive organizational behavior was at a high level in the staff of Shahrekord health centers during the Corona pandemic.  The participatory leadership style was more considered, and had a negative relationship with the stress of Covid-19. Therefore, it seems that it will be possible to establish a correct management style and positive organizational behavior by reducing the stress of Covid-19.